2015
DOI: 10.1186/s40200-015-0216-4
|View full text |Cite
|
Sign up to set email alerts
|

Change in the prevalence of metabolic syndrome in a population of medical students: 6-year follow-up

Abstract: Students of a university hospital were assessed in 2007 and later in 2013 to determine the prevalence of metabolic syndrome. Statistical analysis was done with SPSS version 17.0.A total of 213 students were evaluated in both 2007 and 2013 (48.3 % women and 51.7 % men). The diagnosis of overweight and obesity increased from 24.9 to 37.1 % (p < 0.05), central obesity from 17.8 to 28.6 % (p < 0.05), and prevalence of metabolic syndrome from 9.8 to 14.5 % (p ≥ 0.05); up to 20 % in male gender. It is important to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
1
5
2
Order By: Relevance
“…14,17,18,40 One of those studies was the CARMELA (Cardiovascular Risk Factor Multiple Evaluation in Latin America) multicenter study that evaluated general populations in seven Latin American cities. 14 The MS prevalence found in this study was close to the prevalence rates reported in a sample of health professionals in Brazil (12.8%) 30 and among medical students in Mexico (14.5%) 31 and Ecuador (7.5%). 33 Nonetheless, the overall MS frequency found in this study was lower than the frequencies observed in young people (20-39 years) within the general population (23.8%) 16,20 and in health professionals who worked at health institutions in Mexico (>30%), [25][26][27][28][29] and lower than the 25.8% reported in another multicenter study on South American cities (subjects 35-44 years old).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…14,17,18,40 One of those studies was the CARMELA (Cardiovascular Risk Factor Multiple Evaluation in Latin America) multicenter study that evaluated general populations in seven Latin American cities. 14 The MS prevalence found in this study was close to the prevalence rates reported in a sample of health professionals in Brazil (12.8%) 30 and among medical students in Mexico (14.5%) 31 and Ecuador (7.5%). 33 Nonetheless, the overall MS frequency found in this study was lower than the frequencies observed in young people (20-39 years) within the general population (23.8%) 16,20 and in health professionals who worked at health institutions in Mexico (>30%), [25][26][27][28][29] and lower than the 25.8% reported in another multicenter study on South American cities (subjects 35-44 years old).…”
Section: Discussionsupporting
confidence: 83%
“…[26][27][28] However, the frequency of AO observed in this study is higher than that reported in university students in the United States (22%) 43 and in medical students from Mexico (17.8%). 31 Moreover, the frequency of AO in this study was less than the frequencies observed in medical students from Ecuador (43.2%) 33 and in young health professionals (74.6% younger than 40 years) in Brazil (55.4%). 30 However, the frequency of low HDL-C in our study was higher than that observed in university students from the United States (12.6%) 43 and in young Brazilian health professionals (23.8%) 30 ; and it was lower than the frequency reported in Ecuadorian medical students (31.8%) 33 and in medical students from Mexico (59.1%).…”
contrasting
confidence: 66%
See 2 more Smart Citations
“…Studies have investigated the relationship of MetS and its components with baPWV [7, 2224]. Most have reported increased baPWV in subjects with MetS or with a greater number of MetS components.…”
Section: Introductionmentioning
confidence: 99%